Exploring the impact of social dating applications on relationships during the Covid-19 pandemic among young adults - Alisya, Yahaya; Cheow, Zhi Yang; Chong, Qiao Lin; Chow, Qian Yu; Ho, Kar Fai (2022)
Since 2020, the pandemic has challenged and transformed the framework of dating due to restrictions such as social distancing and stay at home order, resulting in an even higher spike of increase among the most-used dating applications all over the world. In this sense, people used social dating applications as one of the ways to conduct social interactions. In this research, researchers aim to explore the impact of dating applications on relationship, as well to analyse the intention of usage among young adults during the Covid-19 pandemic. A qualitative research approach is adopted in this study. Phenomenology is used to study the guidelines of the factors related to social interaction among young adults using Tinder and Baituljannah on relationships. Purposing sampling is used to obtain detailed data through in-depth interview. Six Malaysian young adults aged between 18 to 35 who used Tinder and Baituljannah during the pandemic were chosen to be interviewed. Based on the findings, Tinder and Baituljannah had a substantial influence on the establishment of romantic relationships, mainly due to lack of emotional wellbeing and absence of positive reinforcement from the immediate environment. A hook-up culture is developed where a sense of reluctance and hesitation showed despite the need of sexual encounters when in isolation. Friendship forming also was the most common activity. Furthermore, the intentions to use Tinder and Baituljannah were to seek for friendships and romantic relationships due to boredom, loneliness and need for affection crave. Using social dating applications while already in a relationship was unfavourable due to low tolerance, and social dating applications were not trustworthy and preferable. The research’s findings might useful for future researchers as a reference to emphasise the impact of social dating applications on relationships among young adults. Future studies could explore the sexual desire of social dating applications during the isolation period to further develop a new finding.